2022
DOI: 10.1097/prs.0000000000009617
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of sensory nerve coaptation in DIEP flap breast reconstruction evaluated using the BREAST-Q

Abstract: Background: Sensory nerve coaptation in autologous breast reconstruction positively affects sensory recovery in the reconstructed breast. However, patient-reported outcomes are lacking and no conclusions on the clinical relevance of nerve coaptation could be drawn. The aim of this study was to evaluate the clinical relevance of nerve coaptation in deep inferior epigastric perforator (DIEP) flap breast reconstruction. Methods: A prospective cohort study was conducted of patients undergoing innervated or nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These findings are in line with many previous studies which have found significant correlation between increased breast sensitivity and increased BREAST-Q scores and patient-reported quality of life. 31,32,33 Although not significant, psychosocial and sexual wellbeing scores also increased. There is a myriad of reasons for this, and many of which are patient-dependent, but it is likely that oncologic treatments likely played a not insignificant role in the lower absolute increases for these two categories.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…These findings are in line with many previous studies which have found significant correlation between increased breast sensitivity and increased BREAST-Q scores and patient-reported quality of life. 31,32,33 Although not significant, psychosocial and sexual wellbeing scores also increased. There is a myriad of reasons for this, and many of which are patient-dependent, but it is likely that oncologic treatments likely played a not insignificant role in the lower absolute increases for these two categories.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…1). 15–91 A list of all included studies is available in Supplemental Digital Content 3. ( See table, Supplementary Digital Content 3 , which displays characteristics and references of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A larger and prospective follow-up study confirmed that quality of life improves in patients with innervated DIEP flap breast reconstruction. On average, patients with immediate and delayed innervated DIEP flap breast reconstruction score higher on the BREAST-Q domain “Physical Wellbeing Chest” compared with their non-innervated counterparts ( 9 ). Multiple other studies have aimed to assess sensation as a patient-reported outcome, however, in the vast majority, unspecific and non-validated measures were applied that poorly reflect qualitative appraisal of sensation in reconstructed breasts ( 87 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, a renewed interest in sensory recovery after breast reconstruction resulted in vastly increasing public and scientific interest. Currently, sensory nerve coaptation is increasingly considered a meaningful addition to modern era autologous breast reconstruction, both in immediate as well as delayed autologous breast reconstruction ( 9 ). Multiple systematic reviews unanimously demonstrate that sensory nerve coaptation improves postoperative breast sensation, and secondarily improves patient-reported quality of life ( 10 - 14 ).…”
Section: Introductionmentioning
confidence: 99%